Assessing early processing of eye gaze in schizophrenia: measuring the cone of direct gaze and reflexive orienting of attention. Issue 2 (4th March 2017) - Seymour, Kiley; Rhodes, Gillian; McGuire, Jonathan; Williams, Nikolas; Jeffery, Linda; Langdon, Robyn
ABSTRACT: Introduction: The accurate discrimination of another person's eye-gaze direction is vital as it provides a cue to the gazer's focus of attention, which in turn supports joint attention. Patients with schizophrenia have shown a "direct gaze bias" when judging gaze direction. However, current tasks do not dissociate an early perceptual bias from high-level top-down effects. We investigated early stages of gaze processing in schizophrenia by measuring perceptual sensitivity to fine deviations in gaze direction (i.e., the cone of direct gaze: CoDG) and ability to reflexively orient to locations cued by the same deviations. Methods: Twenty-four patients and 26 controls completed a CoDG discrimination task that used realistic direct-face images with six fine degrees of deviation (i.e., 3, 6 or 9 pixels to the left and right) and direct gaze, and a gaze cueing task that assessed reflexive orienting to the same fine-grained deviations. Results: Our data showed patients exhibited no impairment in gaze discrimination, nor did we observe a reduced orienting response. Conclusions: These results suggest that while patients may suffer deficits associated with interpreting another person's gaze, the earliest processes concerned with detecting averted gaze and reflexively orienting to the gazed-at location are intact.